Can a theory-based intervention lead primiparous women to decide to have a normal vaginal delivery? A randomized controlled trial - Rashin Pourashraf; Masoumeh Abbasi-Shavazi; Mahboubeh Valiani; Sara Jambarsang; Hossein Ali Sadeghian (Journal of Education and Health Promotion)
Introduction: Although cesarean section (CS) plays an important role in reducing the complications and mortality of childbirth, the increase in unnecessary CSs is an indicator of the improper functioning of the health system. This study aimed to measure the effect of an educational intervention based on the theory of planned behavior (TPB) on the intention and type of delivery of primiparous pregnant women. Materials and Methods: This was conducted as a randomized controlled trial in Isfahan city, Iran. In total, 112 primiparous pregnant women participating in childbirth preparation classes were divided into two intervention and control groups by nonrandom sampling method. The intervention group received an educational intervention that included a combination of childbirth preparation classes based on TPB during the 16th to 38th weeks of pregnancy. The data were completed in the form of an online survey using a validated self-report questionnaire and analyzed in SPSS software version 24. The significance level of the tests was considered as P < 0.05. Results: The average score of attitude, subjective norms, and perceived behavioral control in the intervention group significantly increased after intervention (P < 0.05). Physicians, spouses, and parents were the most important sources of social norms for selecting the type of delivery for pregnant women in both groups before and after the intervention. There was a significant difference between the intention of women in the intervention group, before and after the intervention (P = 0.031), but no significant difference was observed between the two groups regarding the type of delivery (P = 0.556). Conclusion: Reconstructing childbirth preparation classes based on TPB improved the intention and other predictive structures of TPB in the intervention group, but the final behavior of the two groups regarding the type of delivery was the same. It seems that the stressful conditions of delivery, along with the final opinion of the physicians, are effective in choosing the final type of delivery.